Some Aspects of the Evolution of the Archean Crust - Young, G. (Geoscience Canada, 1978)
Summary The geologic record of the Archean in the Superior Province of Canda is divisible into two major portions; an older, high grade basement (>3.5 Ga), and younger (3.0 Ga to 2.6 Ga) rocks that are arranged in easterly-trending zones (Ga, Gigayear, is used to mean 109 years). The younger rocks comprise alternating volcanic (low grade greenstone superbelts) and sedimentary (paragneiss superbelts) terrains. The contrasting lithologie and metamorphic nature of the superbelts is tentatively explained in terms of a mantle convection cell system. Closely analogous Archean assemblages of southern Africa developed about 0.5 Ga earlier, attesting to the heterogeneous nature of the Archean crust and its diachronous evolution in different parts of the world.